CHARACTERISTICS OF MARSHALL ON AC-BC USE THE ANALOG AND DIGITAL TEST EQUIPMENT - Aditama, Akhmad Taufik; Sulistyono, Sonya; Badriani, Ririn Endah (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The strength of the surface pavement can be seen from Marshall Characteristics using Marshall test equipment. Equipment type for Marshall Test can be analog and digital. Digital test equipment using the computer system, and minimize operator/ laboratory intervention for maximum efficiency. The reading of the data was done manually on analog test equipment, so it is very dependent on operator skill. This study examined a mixture of AC-BC using analog and digital Marshall Test equipment, to determine result of Marshall Characteristic. Methods of Marshall Test, material test, mix of bitumen and aggregate follow the guidelines in the Indonesian National Standard (SNI). Results of preliminary test obtained optimum bitumen content of 6,75%, and then the sample is made of 28 pieces (2 x 14). The analysis results of the average difference in the two shows there is no real difference in the Marshall Characteristics of the testing results using analog and digital test equipment. Estimation results of Marshall Characteristics using analog test equipment acquired: stability = + 208,26 kg, Flow = + 0,29 mm dan MQ = + 40,07 kg/mm. Digital test equipment acquired: stability = + 175,47 kg, Flow = + 0,48 mm dan MQ = + 60,93 kg/mm.